Some Weaknesses Associated with the Use of Textbooks - Munawaroh, Hidayatul; Aisyah, Siti (IKIP PGRI Bojonegoro, 2024)
Textbooks have a wide range of complex issues, from outdated information to cultural biases. Identifying these drawbacks provides a useful lens through which to assess the usefulness and suitability of textbook-based instruction in contemporary classrooms. The objectives of this research are to know the weaknesses associated with the use of textbooks and to know does the function of the textbook works as it should or not. This research uses the quantitative design and uses the questionnaire with the Likert Scale. The respondents are twenty-five teachers. The result of this research is completed and included in the “Good” Categories with a total score / Y x 100, or 1622 / 22500 x 100. That is 72,1 %. Fewer weaknesses are identified in the textbook. So, it can be concluded that weaknesses associated with the use of textbooks are a few and the function of the textbook works as it should.